Luminal plant sterol promotes brush border membrane-to-lumen cholesterol efflux in the small intestine - Nakano, Takanari (J Clin Biochem Nutr, 2018)
Plant sterols are used as food additives to reduce intestinal cholesterol absorption. They also increase fecal neutral sterol (FNS) excretion irrespective of the absorption inhibition. Intestine-mediated reverse cholesterol transport, or trans-intestinal cholesterol efflux (TICE), provides the major part of the increase of FNS excretion. However, it is unknown whether plant sterols stimulate TICE or not. We have shown previously that TICE can be evaluated by brush border membrane (BBM)-to-lumen cholesterol efflux. Thus, we examined whether luminal plant sterols stimulate BBM-to-lumen cholesterol efflux in the intestinal tract or not in mice. Cannulated upper jejunum that had been pre-labeled with orally given (3)H-cholesterol, was flushed and perfused to collect (3)H-cholesterol effluxed back into the lumen from the BBM to estimate the efflux efficiency. Adding 0.5 mg/ml of plant sterols, but not cholesterol, in the perfusion solution doubled the efflux. Plant sterols enter the BBM and are effluxed back to the lumen rapidly, in which process cholesterol transporters in the BBM are involved. We thus speculate that phytosterols alter cholesterol flux in the BBM; thereby, increases BBM-to-lumen cholesterol efflux, resulting in the increased TICE.